Comparison of Thin Layer Hydration and Dispersion Method of Transfersome Formulation Containing Hyaluronic Acid and Glutathione as Antioxidant - Dian Ermawati; Adhyatmika; Yuniarti, Nunung; Teuku Nanda Saifullah Sulaiman (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2026)
Glutathione is a tripeptide (L-ᵞ-glutamyl-L-cysteinyl-glycine) that serves as an antioxidant in the body and can be coupled with hyaluronic acid for anti-aging purposes. Glutathione, being hydrophilic, encounters challenges in penetrating the stratum corneum barrier to access the deeper epidermal layers; thus, a transfersome delivery mechanism is requisite. This study aimed to examine the synthesis of transfersome containing glutathione and hyaluronic acid using the thin layer hydration method and the dispersion method. The characteristics measured included organoleptic properties, particle size, zeta potential, polydispersity index (PDI), entrapment efficiency, and antioxidant activity assessed via the DPPH method. Particle size and PDI were found to be 124.5 ± 14.11 nm, 0.367± 0.07 for thin layer hydration method and 583.03 ± 32.41 nm, 0.595 ± 0.03 for dispersion method respectively. Entrapment efficiency showed that the thin layer hydration method was greater at 35.65% ± 3.54 compared to the dispersion method at 19.10 % ± 1.13. Antioxidant activity showed the inhibition in thin layer hydration and dispersion method was 42.48% ± 0.84 and 41.23% ± 2.09 respectively. In conclusion, the thin layer hydration method gives more optimal results than the dispersion method.